1987
DOI: 10.1073/pnas.84.20.7300
|View full text |Cite
|
Sign up to set email alerts
|

Insulin exerts metabolic and growth-promoting effects by a direct action on the liver in vivo: clarification of the functional significance of the portal vascular link between the beta cells of the pancreatic islets and the liver.

Abstract: The functional significance of the portal vascular link between the beta cells of the pancreatic islets and the liver has not been established. Previous studies indicated that insulin does not acutely regulate glucose metabolism by a direct hepatic effect. More recent observations suggest that the role of insulin in regulating body growth may be mediated, at least in part, by the liver. Our experiments were designed to test whether insulin can promote body growth and regulate glucose metabolism by a direct hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 50 publications
3
27
1
Order By: Relevance
“…Insulin, thyroid hormones and low concentrations of glucocorticoids potentiate GH-stimulated IGF-I mRNA expression, whereas glucagon and high concentrations of glucocorticoids inhibit basal or GH-stimulated IGF-I expression (Tollet et al 1990, Boni-Schnetzler et al 1991, Houston & O'Neill 1991, Denver & Nicoll 1994, Brameld et al 1995, Beauloye et al 1999. In vivo data support a physiologically significant positive role for insulin in the regulation of GH sensitivity (Griffen et al 1987). Within the hepatocyte, changes in GH sensitivity occur at both the receptor and post-receptor level (Thissen et al 1994.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Insulin, thyroid hormones and low concentrations of glucocorticoids potentiate GH-stimulated IGF-I mRNA expression, whereas glucagon and high concentrations of glucocorticoids inhibit basal or GH-stimulated IGF-I expression (Tollet et al 1990, Boni-Schnetzler et al 1991, Houston & O'Neill 1991, Denver & Nicoll 1994, Brameld et al 1995, Beauloye et al 1999. In vivo data support a physiologically significant positive role for insulin in the regulation of GH sensitivity (Griffen et al 1987). Within the hepatocyte, changes in GH sensitivity occur at both the receptor and post-receptor level (Thissen et al 1994.…”
Section: Introductionmentioning
confidence: 54%
“…Insulin potentiated the GH response at the level of IGF-I protein secretion into medium in chicken and rat hepatocytes (Houston & O'Neill 1991, Villafuerte et al 1992. Studies in diabetic mammals support a requirement for normal portal insulin levels to maintain liver IGF-I production, plasma IGF-I levels and growth (Griffen et al 1987). As far as we are aware, no study in any tetrapod species has shown inhibition by insulin of basal or GH-dependent hepatocyte IGF-I mRNA expression or protein secretion.…”
Section: Discussionmentioning
confidence: 92%
“…Insulin secretion into the hepatic portal vessels results in exposure of the liver to high concentrations of insulin. Maintenance of insulin levels is necessary to maintain liver GH sensitivity, liver igf1 gene expression, blood Igf1 levels, and growth (Griffen et al 1987, Rodgers et al 1994, Thissen et al 1994, Phillips et al 1998, Butler et al 2003. Insulin levels in the portal vessels are also elevated in fish (Plisetskaya & Sullivan 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolically responsive hormones link the anabolic/ catabolic state of the animal to liver GH sensitivity. Insulin directly increases hepatocyte Igf1 production, and strongly increases hepatocyte responsiveness to GH in vivo (Griffen et al 1987, Butler et al 2003, and in mammalian and avian primary hepatocyte culture (Tollet et al 1990, Boni-Schnetzler et al 1991, Houston & O'Neill 1991, Phillips et al 1998. Glucocorticoids induce liver GH resistance (Rodgers et al 1994, Brameld et al 1995, Beauloye et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…A role for insulin in the growth hormone signal transduction mechanism has been proposed by a number of investigators (Daughaday et al 1976, Scott & Baxter 1986, Griffen et al 1987, Salamon et al 1989) and the lack of response to growth hormone by diabetic animals may be an indirect consequence of insulin deficiency.…”
Section: Discussionmentioning
confidence: 99%